Customer Satisfaction toward Online Purchasing Services: Evidence from Small & Medium Restaurants - Carol Y Lu; Dwi Suhartanto; Arie Indra Gunawan; Brendan T Chen (Politeknik Negeri Bandung, 2020)
This study examines shopper satisfaction toward an online purchasing model in small and medium restaurants (SMRs), including the quality of e-service and food, with perceived value as the determinants. For this research purpose, 392 data gathered from online restaurant shoppers in Bandung, Indonesia. This study adopts the Structural Equation Model (PLS) to evaluate shopper satisfaction relations with its determinants as well as consequences. The results uncover that both the quality of e-service and food on shopper satisfaction is essential, and disclose the partial mediation function of perceived value to assess the relationship between both qualities on shopper satisfaction. This study offers a guide to SMR managers to enhance their business performance by focusing on the quality of food, instead of focusing on both the quality of e-service and food. In terms of online service-based businesses, this research implies that the SMRs need to collaborate with reliable online platform service providers.